2001
DOI: 10.1203/00006450-200101000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in Neonatal Acylcarnitine Profile

Abstract: Electrospray-tandem mass spectrometry represents a powerful method for detection of inborn errors of fatty acid metabolism. In the present study, it was used to examine neonatal carnitine metabolism, which reflects fatty acid metabolism. In 70 healthy neonates, blood samples were taken from the umbilical cord and by heel-stick puncture in full-term neonates on postnatal d 5. Cord blood specimens were also obtained from 15 preterm and 10 small-for-gestational-age infants. Acylcarnitine concentrations were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
4
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 20 publications
2
50
4
2
Order By: Relevance
“…A negative correlation with BW and GA was also found in plasma for C 14 Mode of delivery and AC profile. The Kruskal-Wallis test revealed significant differences emerged for some ACs in relation to whether the mode of delivery was vaginal (VD) or cesarean section (CS).…”
Section: Articlesmentioning
confidence: 72%
See 2 more Smart Citations
“…A negative correlation with BW and GA was also found in plasma for C 14 Mode of delivery and AC profile. The Kruskal-Wallis test revealed significant differences emerged for some ACs in relation to whether the mode of delivery was vaginal (VD) or cesarean section (CS).…”
Section: Articlesmentioning
confidence: 72%
“…Box and whisker plots of characteristic short-, medium-, and long-chain acylcarnitines (ACs) in dried blood spots (DBS): (a) free carnitine, (b) C 2 , (c) 2-methylbutyril, (d) C 6 , (e) C 8 , (f) C 10 , (g) C 12 , (h) C 14 , and (i) C 16 . The values are stratified by gestational age (GA) group, from G1 to G4.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Many laboratories acquire FC within the full scan of acylcarnitines (m/z 218 -500), whereas others analyze FC as a separate analyte with its own optimized settings and scan function, such as SRM. Monitoring FC is important for several reasons in addition to disease detection (49,96 ). For example, increased FC in QC samples suggests hydrolysis of acylcarnitines during storage.…”
Section: Fc Fc Is Detected By Use Of a Pre 85 Scan Or Pre 103 Scanmentioning
confidence: 99%
“…In the experimental setting metabolomic studies performed in animal models of hypoxia reoxygenation have shown that oxidative stress associated metabolites strongly correlate with brain injury. The most specific and reliable biomarkers identified have been isoprostanes, neuroprostanes, non-protein bound iron, and 4-HNE proteins adducts [15][16][17]. F2-isoprostanes have been determined to be both biomarkers and mediators of oxidative stress in numerous diseases [18].…”
Section: Introductionmentioning
confidence: 99%